Exploring tomato Solanum pennellii introgression lines for residual biomass and enzymatic digestibility traits. Issue 1 (December 2016) - Caruso, G.; Gomez, L.; Ferriello, F.; Andolfi, A.; Borgonuovo, C.; Evidente, A.; Simister, R.; McQueen-Mason, S.; Carputo, D.; Frusciante, L.; Ercolano, M.
Abstract Background Residual biomass production for fuel conversion represents a unique opportunity to avoid concerns about compromising food supply by using dedicated feedstock crops. Developing tomato varieties suitable for both food consumption and fuel conversion requires the establishment of new selection methods. Results A tomatoSolanum pennellii introgression population was assessed for fruit yield, biomass phenotypic diversity, and for saccharification potential. Introgression lines 2–5, 2–6, 6–3, 7–2, 10–2 and 12–4 showed the best combination of fruit and residual biomass production. Lignin, cellulose, hemicellulose content and saccharification rate showed a wide variation in the tested lines. Within hemicellulose, xylose value was high in IL 6–3, IL 7–2 and IL 6–2, whereas arabinose showed a low content in IL 10–2, IL 6–3 and IL 2–6. The latter line showed also the highest ethanol potential production. Alkali pre-treatment resulted in the highest values of saccharification in most of lines tested, suggesting that chemical pretreatment is an important factor for improving biomass processability. Interestingly, extreme genotypes for more than one single trait were found, allowing the identification of better genotypes. Cell wall related genes mapping in genomic regions involved into tomato biomass production and digestibility variation highlighted potential candidate genes. Molecular expression profile of few of them provided useful information about challenged pathways. Conclusions The screening ofS. pennellii introgression population resulted very useful for delving into complex traits such as biomass production and digestibility. The extreme genotypes identified could be fruitfully employed for both genetic studies and breeding.